Cranberry Extract as a Supplemented Food in Treatment of Oxidative Stress and Breast Cancer Induced by N-methyl-N-nitrosourea in Female Virgin Rats - Sylvia A. Boshra; Mohammed Abdalla Hussein (International Journal of Phytomedicine, 2016)
Breast cancer is the most common cancer and a major cause of death in women. The present study was designed to evaluate the antioxidant and anticancer potential of cranberry extract against N-methyl-N-nitrosourea (MNU) induced mammary carcinoma in rats. The tumor was induced in Female virgin rats of age 50 days by single dose of MNU (50mg/kg.b.w i.p.). After 85 days; all rats developed at least one tumor. Animals were treated with cranberry extract (400 and 600 mg/kg.b.w.orally) and tamoxifen (2mg/kg.b.w. i.p) for 4 weeks (from day 86 to day 113). MNU treatment resulted in a significant decrease (p < 0.05) in blood hemoglobin (Hb), red blood cells (RBC), platelets (PLTs) as well as blood, liver and breast catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD). However, MNU treatment resulted in a significant increase in White blood cells (WBC) as well as plasma, liver and mammary tissue gamma glutamyl transferase (GGT), lactate dehydrogenase (LDH), hexosamine, sialic acid and thiobarbituric acid reactive substances (TBARs). Upon administration of the cranberry extract, the levels of WBC, GGT, LDH, hexosamine, sialic acid, TBARs, Hb, RBC, PLTs, CAT, GPx and SOD were significantly normalized. Histopathological changes also confirmed the formation of tumor tubules and neovascularization after the MNU treatment. Cranberry extract administration significantly reduces the growth of MNU-induced mammary tumors, and therefore has strong potential as a useful therapeutic regimen for inhibiting breast cancer development. Comparing the beneficial effect of cranberry extract with that of MNU-induced breast cancer, cranberry extract showed antitumor and antioxidant activity indicated by the measured biochemical parameters and the histopathological examination of mammary tissue. The results of the present study indicate that cranberry extract possesses strong anticancer effects through its role in modulating glycoprotein components and the levels of oxidative stress biomarkers. Cranberry exerted a stronger anticancer effect at the dosage of 600 mg/kg body weight than at dosage 400 mg/kg body weight.